2006
DOI: 10.1002/hyp.6216
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation alters the hydraulic and biogeochemical characteristics of small lowland Amazonian streams

Abstract: Abstract:We investigated how clearing of the tropical rainforest for cattle pasture along small, terra firme lowland streams in the Brazilian Amazon influenced stream hydraulic characteristics, solute concentrations and uptake of dissolved inorganic nitrogen and phosphorus. Measurements of stream channel structure, hydraulic properties and nutrient uptake were obtained from short-term conservative and non-conservative solute injections and an in-stream transport model in two watersheds with pairs of similar-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
3
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 57 publications
5
38
3
7
Order By: Relevance
“…The effects of change in land use on the biogeochemistry have also been described in the literature for both major rivers and streams. It has been shown that these changes affect nitrate, ammonium, calcium, potassium and aluminum concentrations in streams located in temperate (Wang et al 2006, Kamisako et al 2008, Rai et al 2010) and tropical regions (Neill et al 2006, Andrade et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of change in land use on the biogeochemistry have also been described in the literature for both major rivers and streams. It has been shown that these changes affect nitrate, ammonium, calcium, potassium and aluminum concentrations in streams located in temperate (Wang et al 2006, Kamisako et al 2008, Rai et al 2010) and tropical regions (Neill et al 2006, Andrade et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In the Cerrado of Central Brazil and in southern Amazônia the process of deforestation for the establishment of agriculture and pastures has caused serious alterations in aquatic habitats (Williams et al, 1997;Neill et al, 2001Neill et al, , 2006. The removal of native vegetation can alter significantly the biogeochemical processes of soils and, as a consequence, increase the amount of particulate and dissolved material in streams (Williams et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…No período de chuvas, os nutrientes presentes no solo são carregados para os corpos d'água e a serapilheira da fl oresta é uma fonte importante de DOC (SCHWENDENMANN; VEL-DKAMP, 2005). A presença de gramíneas nos riachos também leva a um aumento na carga orgânica (NEILL et al, 2006). Além disso, a entrada de matéria orgânica de dejetos animais está relacionada ao escoamento superfi cial (BIGGS; DUNNE; MURAOKA, 2006).…”
Section: áGua Dos Riachos Da Bacia Do Rio Corumbataíunclassified